THE LEGAL PROTECTION OF PATENTS ON PHYTOPHARMACEUTICAL PRODUCTS IN INDONESIA: CASE STUDIES AND THEORETICAL PERSPECTIVES - Tjandrawinata, Raymond R.; Budi, Henry Soelistyo (International Journal of Social Service and Research, 2024)
Indonesia has great potential in the development of biowealth-based phytopharmaceutical products, considering its rich natural wealth and traditional medicine traditions. This study uses theories of legal utilitarianism, distributive justice, and legal positivism to explore the challenges facing Indonesia, as well as opportunities for more inclusive and adaptive reforms. This analysis employs a normative juridical approach, focusing on the analysis of written laws, regulations, doctrines and legal interpretations related to patent protection for phytopharmaceutic products. This approach enables a thorough understanding of the patent legal framework in Indonesia and its practical implementation. The case study method is used to evaluate several patents registered with the Directorate General of Intellectual Property (DJKI). The results show that Indonesia is facing a number of complex legal challenges in the patent registration process, ranging from barriers to novelty criteria and inventive steps to lengthy administrative processes. In addition, Indonesia needs to strengthen its national patent system and intellectual property protection strategies to ensure that local communities benefit fairly from the use of their traditional knowledge. This research could investigate how these mechanisms influence innovation within local communities and their role in fostering sustainable practices.